Інноваційні процеси як довгострокові джерела формування ринкової вартості підприємства - Єфімова, Г. В.; Пащенко, О. В.; Iefimova, G. V.; Pashchenko, O. V. (Видавництво Львівської політехніки, 2017)
Розглянуто формування ринкової вартості промислового підприємства на основі інноваційних процесів, розкрито механізм комплексного впливу усіх типів інноваційних процесів на формування ринкової вартості підприємства у довгостроковому періоді та типи інноваційних процесів та їх вплив на зростання вартості промислового підприємства. Досліджено стадії життєвого циклу інновації. Формалізовано модель оцінки ринкової вартості у довгостроковому періоді на основі інноваційних процесів, визначено склад та взаємозв’язок функцій цієї моделі, що дає можливість забезпечити цілеспрямоване управління формуванням ринкової вартості промислового підприємства

Formation of the industrial enterprises market value of the based on innovative processes is considered. The aim of the research is disclosure of the combined effect mechanism of all types of innovative processes for the formation of the enterprise market value in the long term. Types of innovative processes and their impact on the industrial enterprise value rising are considered. Stages of innovation life cycle are investigated. To enhance the impact of product innovations on the rising cost of industrial enterprise can in case of application process and allocation innovation at different stages of the innovation. Enterprise value in the long term is considered as a function of the cash flows. The model of estimation of the enterprise market value in the long term based on innovative processes is formalized. The composition and interrelation of the functions of this model are determined. It makes possible to provide targeted management of the formation of the market value of a production enterprise. The introduction of a management system of the industrial enterprise value in the long term based on the innovative processes will facilitate its adaptation to the dynamic processes of market changing. All of this will provide growth of the enterprise market value through an increase of assets value and through ensure growth future cash flows. Implementation of innovative active development strategy ensures long-term presence the industrial enterprise on market.
Innovation processes as long-term sources of formation of the enterprise market value
Keywords: інновації; інноваційні процеси; життєвий цикл інновації; вартість підприємства; грошовий потік; інвестиції; innovation; innovation processes; lifecycle of innovation; enterprise value; cash flow; investments; 338; 658.1